Media Pembelajaran Reading and Listening Berbasis Platform Blogging dalam Pembelajaran Tematik di SD/MI - Rohmah, Miftahur; Indrianto, Nino (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Difficulties in understanding the thematic material experienced by students can affect their learning outcomes. Consequently, there is a necessity to develop learning media that can improve students’ learning outcomes, including through Blogging Platform-based Reading and Listening media. The type of this research was Research and Development using the ADDIE model with several stages, namely analyzing, designing, developing, implementing, and evaluating. This research has succeeded in developing a website-based Reading and Listening media, namely using the Blogging Platform with thematic material (theme 6) at the grade V students of SD/MI (elementary school). From the three validators obtained, this research found an average result of 91% and it was declared to be in the very feasible category. The effectiveness of the media was measured from students’ learning outcomes through the pre-test with an average score of 65 and an average post-test score of 75 and it indicated an increase in value by 15. So, it can be concluded that the Reading and Listening learning media based on the Blogging platform have an effect on improving students’ learning outcomes in thematic learning